Ethics in health care: The practice of defensive medicine - G.A. Ogunbanjo; D. Knapp van Bogaert (South African Family Practice)
Defensive medicine is the practice of diagnostic or therapeutic measures that are conducted primarily as a safeguard against possible malpractice liability, rather than to ensure the health of the patient. Defensive medicine, a significant problem, is discussed in this article. First, an overview of the nature of defensive medicine is provided, with a focus on how it damages the doctor-patient relationship. It has been determined that doctors who utilise defensive medicine ultimately exact more harm than good on the practice of medicine. Finally, it is suggested that through ensuring that the doctor-patient relationship is impenetrable, fear of medical litigation will dissipate. The best antidote to malpractice allegations is ethical clinical practice. Core decisions remain bound in dialogue between the doctor and his or her patient. Continuing the tradition of the therapeutic alliance, informed consent and confidentiality in medical practice will diminish threats of medical liability.